2008
DOI: 10.1007/s10695-008-9254-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical identification of adenohypophyseal cells in the pirarucu (Arapaima gigas), an Amazonian basal teleost

Abstract: The adenohypophysis (AH) of juvenile pirarucu (Arapaima gigas), a representative species of the Osteoglossomorpha (bonytongue fishes, one of the oldest living groups of the teleosts), was studied using histochemical and immunocytochemical methods. The AH is comprised of the pars distalis (PD), without a clear distinction between rostral pars distalis (RPD) and proximal pars distalis (PPD), and the pars intermedia (PI). The neurohypophysis (NH) is positioned on top of the PD and penetrates and branches into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 53 publications
9
27
0
7
Order By: Relevance
“…No positive structures or cells were found in these sections. Furthermore, the specificity of the antisera could also be inferred from the localization of the immunostained cells, which agree with previously reports in other neotropical fish species (Nóbrega 2006; Borella et al 2009). Following immunostaining, the sections were examined and documented using a computerized image analyzer (described above).…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…No positive structures or cells were found in these sections. Furthermore, the specificity of the antisera could also be inferred from the localization of the immunostained cells, which agree with previously reports in other neotropical fish species (Nóbrega 2006; Borella et al 2009). Following immunostaining, the sections were examined and documented using a computerized image analyzer (described above).…”
Section: Methodssupporting
confidence: 90%
“…In this study, we used anti-chum salmon GH, which showed a quite specific immunostaining within the GH cells of S. hilarii , as demonstrated similarly in other teleost fishes. The distribution of GH cells followed the patterns already described in others fish species (Vissio et al 1997; Segura-Noguera et al 2000; Pandolfi et al 2001a; Sánchez-Cala et al 2003; Borella et al 2009). GH-ir cells have been located in the PPD region, either isolated or clustered, and no cross-reactivity of other cell types occurred in S. hilarii .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In P. andruzzii adults the distribution of adenohypophyseal cell types in the three regions of the pituitary appeared in good agreement with that of other teleosts (Agulleiro et al ., ; Borella et al ., ). Prolactin (PRL) and adrenocorticotropic (ACTH) cells were identified in RPD and somatotropic (STH), thyrotropic (TSH) and gonadotropic (FSH and LH) cells in PPD.…”
Section: Discussionmentioning
confidence: 97%
“…In order to understand the rmPOMC-locating pattern in the pituitary gland of the rare minnow, section in situ hybridization was performed, revealing that rmPOMC-positive cells distribute not only in the RPD and PI, but also in the PPD; however, there were only a few cells scattered in, and the corticotropes were dispersed. In most teleosts, such as Atlantic halibut (Hippoglossus hippoglossus, Weltzien et al 2003) and Nile tilapia (Kasper et al 2006), the corticotropes only occupied a small area, among the PN and the Lactotropes, and in pirarucu (Arapaima gigas), which was lack of a distinction between RPD and PPD, the ACTH cells were arranged in dorsal part of pars distalis (PD) region (Borella et al 2009). However, there were also a few POMC-positive cells distributed in the PPD of the less developed vertebrate, Lamprey (Agnatha), and according to immunocytochemical staining, these cells were an ACTH-like type that appeared to be active throughout the life cycle (Nozaki et al 2001).…”
Section: Discussionmentioning
confidence: 99%